2014
DOI: 10.3917/spub.137.0107
|View full text |Cite
|
Sign up to set email alerts
|

Consommation d'alcool en milieu urbain chez les élèves du secondaire en Côte d'Ivoire

Abstract: In the light of the determinants of alcohol consumption and the students'suggestions in our study, it appears essential to involve students in actions concerning alcohol abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…This observation had been made in a study conducted among secondary school students in Lagos 23 . The prevalence found in our study was higher than that reported among secondary school students in Brazil 24 and other African countries 13,21 . However, the current use prevalence found was lower than that reported among high school students in the Peruvian Amazon 25 .…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…This observation had been made in a study conducted among secondary school students in Lagos 23 . The prevalence found in our study was higher than that reported among secondary school students in Brazil 24 and other African countries 13,21 . However, the current use prevalence found was lower than that reported among high school students in the Peruvian Amazon 25 .…”
Section: Discussionsupporting
confidence: 51%
“…23 The prevalence found in our study was higher than that reported among secondary school students in Brazil 24 and other African countries. 13,21 However, the current use prevalence found was lower than that reported among high school students in the Peruvian Amazon. 25 The higher prevalence of alcohol found in our study compared to other substances may be accounted for by the easy access and availability of alcoholic beverages in Benin.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Ils étaient également plus à risque de consommer des drogues (OR = 10,42 IC 95 % = [2,87-37,79]). Une étude menée à Abidjan en Côte d'Ivoire par Dagnan et al en 2011, parmi les élèves du secondaire, a mis en relation la consommation d'alcool et la dépression scolaire [16].…”
Section: Facteurs Associés à L'usage Des Substances Psychoactivesunclassified